Globalization of Plastic and Reconstructive Surgery: A Continent, Country, and State-Level Analysis of Publications. Issue 11 (November 2020) - Liechty, Andrew E.; Sherpa, James R.; Trejo, Jonathan S.; French, Mackenzie M.; Kneib, Cameron J.; Cho, Daniel Y.; Friedrich, Jeffrey B.
Abstract : Background: Over the past decade, there has been a worldwide increase in plastic and reconstructive surgery research as well as increased interest in global collaboration. However, little is known about who is contributing to this global expansion or the trends of individual countries. The aim of our study was to analyze the output of Plastic and Reconstructive Surgery (PRS ) over a decade to elucidate trends in the plastic surgery field. Methods: The country of origin for all first authors of articles published by PRS from 2010 to 2019 were determined and date extracted using PubMed2XL. The change in frequency of publications over the decade by country, continental contributions, as well as state-level analysis within the United States were analyzed. Results: From 2010 to 2019, there were a total number of 8680 publications with an increase in total articles from 747 to 1049 per year. 54 countries contributed over the decade, with the United States producing the most followed by Italy, China, Canada, and the UK. The top producing states were Texas, New York, California, Massachusetts, and Pennsylvania. Conclusions: The last decade (2010–2019) saw a large international increase in research, not only with the total number of publications, but also in the diversity of originating country. Our work shows a shift away from a US-focused journal to incorporate more work from our international colleagues, as research is conducted in centers across the globe.